OsPLS4 Is Involved in Cuticular Wax Biosynthesis and Affects Leaf Senescence in Rice - Zhou, Dahu; Li, Ting; Yang, Yaolong; Qu, Ziyang; Ouyang, Linjuan; Jiang, Zhishu; Lin, Xiaoli; Zhu, Changlan; Peng, Liyuan; Fu, Junru; Peng, Xiaosong; Bian, Jianmin; et al. (Frontiers in Plant Science, 2020)
Leaf senescence is one of the most common factors that affects the growth and yield of rice. Although numerous genes affecting leaf senescence have been identified, few involved in cuticular wax synthesis have been described for rice premature leaf senescence. Here, we cloned and characterized Premature Leaf Senescence 4 (PLS4) in rice (Oryza sativa), which encodes a putative 3-oxoacyl-reductase in the fatty acid biosynthetic pathway. Subcellular localization of OsPLS4 was observed in the chloroplast. A single nucleotide substitution in OsPLS4 reduced leaf cuticular wax, and the expression levels of most wax biosynthesis-associated genes were downregulated. TEM showed chloroplast development were defective in the pls4 mutant. Further investigation revealed that the chlorophyll (Chl) content was reduced in the pls4 mutant compared with the WT and that the photosynthesis rate was lower, which caused ROS dramatic accumulation at the heading stage. These results confirmed premature leaf senescence in pls4 plants. Cold treatment indicated that the mutant was more sensitive than the WT was to cold stress. Together, all the above results indicate that the OsPLS4 mutation affects cuticular wax biosynthesis and chloroplast development in rice, causing reduced cuticular wax and premature leaf senescence. Our identification and characterization of OsPLS4 reveal a new molecular mechanism involved in premature leaf senescence.